A Model of the Effect of the Microbial Biomass on the Isotherm of the Fermenting Solids in Solid-State Fermentation - Barbara Celuppi Marques; Marcelo Calide Barga; Wellington Balmant; Luiz Fernando de Lima Luz Jr; Nadia Krieger; David Alexander Mitchell (Food Technology and Biotechnology, 2006)
We compare isotherms for soybeans and soybeans fermented with Rhizopus oryzae, showing that in solid-state fermentation the biomass affects the isotherm of the fermenting solids. Equations are developed to calculate, for a given overall water content of the fermenting solids, the water contents of the biomass and residual substrate, as well as the water activity. A case study, undertaken using a mathematical model of a well-mixed bioreactor, shows that if water additions are made on the basis of the assumption that fermenting solids have the same isotherm as the substrate itself, poor growth can result since the added water does not maintain the water activity at levels favorable for growth. We conclude that the effect of the microbial biomass on the isotherm of the fermenting solids must be taken into account in mathematical models of solid-state fermentation bioreactors.